THE MECHANICS OF THE TIBETAN PLATEAU - England, P; Houseman, G (1988)
Continental convergence results in compressional deformation over a distance, perpendicular to strike, that is comparable to the length of the convergent boundary. The compressional forces generated by the convergence are resisted, to some extent, by the extensional deviatoric stresses arising from isostatically balanced increases in crustal thickness; as a result a plateau may form, in front of a compressional boundary, whose elevation is limited by the strength of the continental lithosphere. However, the extensional stresses do not exceed the compressional stresses that generate the crustal-thickness contrasts unless there is a major change, either in the convergent velocity or in the potential energy of the elevated region. For the collision of India with Asia, it appears that there has not been a change in the convergent boundary condition sufficient to cause the late-Tertiary to present extension in the region. It is suggested that thermal evolution of the region, involving a delayed convective instability of the base of the thickened lithosphere, could have raised the surface elevation and the potential energy of the Tibetan Plateau, leading to the observed extension there. -Authors